1995
DOI: 10.1007/bf00203398
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of proliferation parameters in in vivo bromodeoxyuridine labelled lung cancers

Abstract: In a series of 44 bronchial biopsies from patients suspected of having endobronchial lung carcinoma, the validity of proliferating cell nuclear antigen (PCNA) and Ki67 antigen as proliferative indicators was evaluated in ethanol fixed, paraffin embedded tissue. The percentages of cells positive for these markers were compared to the in vivo bromodeoxyuridine (BrdU) labelling index. A good correlation was found between PCNA immunoreactivity and BrdU labelling index, while Ki67-antigen expression showed a signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 42 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…In the previous studies, a linear correlation between the percentage of PCNA-positive cells and S + G2 + M or S phase fraction measured by flow cytometry was recorded [9,31]. Also found was a linear correlation between the percentages of PCNA-positive cells and BrdU-labelled cells [27]. These findings suggest that PCNA immunostaining may be used as a marker of cell proliferation in various tumours.…”
Section: Discussionmentioning
confidence: 60%
“…In the previous studies, a linear correlation between the percentage of PCNA-positive cells and S + G2 + M or S phase fraction measured by flow cytometry was recorded [9,31]. Also found was a linear correlation between the percentages of PCNA-positive cells and BrdU-labelled cells [27]. These findings suggest that PCNA immunostaining may be used as a marker of cell proliferation in various tumours.…”
Section: Discussionmentioning
confidence: 60%
“…Our results also showed the presence of a few number of proliferated cells in mice of ages 12 weeks and older as indicated by Ki-67 marker. It was reported that Ki-67 antigen is expressed in all cycling cells, whereas BrdU reflects only the S-phage cells [ 16 ]. Importantly, the amount of proliferative stem cell populations shown in the P1 and 2-week-old mice SGN-NSCs were higher than those seen in the 4-, 12-, and 24-week-old mice SGN-NSCs, which supports the idea that the SGN-NSC spheres derived at an early age in mice contain more mitotic stem cells than those in mice at a later age.…”
Section: Discussionmentioning
confidence: 99%
“…Strong nuclear staining may reflect a replication-associated from of PCNA (Yu et al, 1995). In the studies where alcohol was used as a fixative, a good correlation between PCNA expression and BrdU labelling indices or the flow cytometrically determined S phase fraction is reported because the replication-associated from of PCNA remains in the cell after alcoholic fixation (Coltrera et al, 1993;Tinnemans et al, 1995). In a prospective study on PCNA staining, alcohol fixation may be better than formalin fixation.…”
Section: Discussionmentioning
confidence: 99%